Estado excitado ressonante e mecanismos de relaxação no vidro aluminosilicato de cálcio dopado com Tb³+ e co-dopado com Tb³+ e Yb³+ : estudo com a espectroscopia de espelho térmico - Bianchi, Giselly dos Santos (2014)
Resonant excited-state absorption and relaxation processes in Tb3+-doped and Tb3+/Yb3+-codoped aluminosilicate glasses are quantitatively evaluated. Theoretical models describing the excitation steps, upconversion emission and energy transfer between ions are developed and applied to interpret the results from laser-induced surface deformation using the thermal mirror spectroscopy. For the Tb3+-doped glasses the fluorescence quantum efficiency of level 5D4 was found to be close to unit and concentration independent, while for the level 5D3 it decreases with Tb3+ concentration. Emission spectroscopy measurements supported these results. Excited-state absorption cross-sections are found to be more than three orders of magnitude higher than the ground-state absorption cross-section. For the Tb3+/Yb3+-codoped glasses, measurement of heat generated presented the occurrence of energy down conversion with significant increase of the emission from samples in 980nm. This result suggests that this material is a candidate to be used as a sensitizer to improve the efficiency of the current solar cells based on silicon. Conventional spectroscopic measurements were performed to validate the results obtained with thermal mirror method. In conclusion, the experimental and theoretical results of this study demonstrated that thermal mirror spectroscopy is an advantageous analytical tool for quantitative measurement of relaxation processes difficult to quantify by conventional spectroscopic techniques. Furthermore, the glass prepared is promising for the development of a new generation of hybrid solar cells have the potential to be more effective compared with today's silicon.